A Typological Analysis of Dairy Farms Based on Bulk Milk Price - Costa, V. D. V.; Martinelli, R. R.; Bánkuti, F. I. (Tropical Animal Science Journal, 2022)
This study sought to examine the relationship between typological characteristics of dairy farms and the price received per liter of bulk milk in transactions with processing companies. During a period from January to March 2018, a total of 143 dairy farmers in western São Paulo State were interviewed on-site using a semi-structured questionnaire containing questions regarding structural, productive, and socioeconomic characteristics of farms and farm operators. Dairy farms were classified into two groups: G1 (n= 129), farms paid below the regional average price per liter of milk; and G2 (n= 14), farms paid above the regional average price per liter of milk. Then, factor analysis was used to extract factors associated with each dairy farm group. Three factors were identified: F1, Milk volume and quality; F2, Road conditions; and F3, Production area. Mean factor scores were compared by the Mann–Whitney U-test (p